Probability Distribution of Arm Trajectory for Motion Estimation and Gesture Recognition - Wan Khairunizam, Wan Ahmad; Mohd Azri, Abdul Aziz; Shahriman, Abu Bakar; Siti Khadijah, Zaaba; Zuwairie, Ibrahim; Zulkifli, Md Yusof; Ismail, Ibrahim; Jameel Abdulla, Ahmed Mukred; N. Mokhtar (American Scientific Publishers, 2013)
Link to publisher's homepage at http://www.ingentaconnect.com/content/asp/asl